Hemoglobin Serves to Protect Plasmodium Parasites from Nitric Oxide and Reactive Oxygen Species. (1st July 2005) - Sobolewski, Peter; Gramaglia, Irene; Frangos, John A.; Intaglietta, Marcos; van der Heyde, Henri C.
Abstract : ABSTRACT: Our understanding of how the host immune response kills Plasmodium, the causative agent of malaria, is limited and controversial. One widely held belief is that reactive oxygen species are crucial for controlling parasite replication. One of the hallmarks of blood-stage malaria is the cyclic rupture of erythrocytes by the parasite, which releases free hemoglobin into the circulation. We propose that this free hemoglobin, as well as the hemoglobin within the erythrocyte and surrounding the parasite, effectively shields Plasmodium from reactive oxygen species well in excess of those achievable in vivo.